Macrophages in Injured Skeletal Muscle: A Perpetuum Mobile Causing and Limiting Fibrosis, Prompting or Restricting Resolution and Regeneration - Bosurgi, Lidia; Manfredi, Angelo A.; Rovere Querini, Patrizia (Frontiers in Immunology, 2011)
Macrophages are present in regenerating skeletal muscles and participate in the repair process. This is due to a unique feature of macrophages, i.e. their ability to perceive signals heralding ongoing tissue injury and to broadcast the news to cells suited at regenerating the tissue such as stem and progenitor cells. Macrophages play a complex role in the skeletal muscle, probably conveying information on the pattern of healing which is appropriate to ensure an effective healing of the tissue, yielding novel functional fibers. Conversely, they are likely to be involved in limiting the efficacy of regeneration, with formation of fibrotic scars and fat replacement of the tissue when the original insult persists. In this review we consider the beneficial versus the detrimental actions of macrophages during the response to muscle injury, with attention to the available information on the molecular code macrophages rely on to guide, throughout the various phases of muscle healing, the function of conventional and unconventional stem cells. Decrypting this code would represent a major step forward towards the establishment of novel targeted therapies for muscle diseases.